Different Short-Term Mild Exercise Modalities Lead to Differential Effects on Body Composition in Healthy Prepubertal Male Rats. (28th January 2015) - Sontam, D. M.; Vickers, M. H.; O'Sullivan, J. M.; Watson, M.; Firth, E. C.
Abstract : Physical activity has a vital role in regulating and improving bone strength. Responsiveness of bone mass to exercise is age dependent with the prepubertal period suggested to be the most effective stage for interventions. There is a paucity of data on the effects of exercise on bone architecture and body composition when studied within the prepubertal period. We examined the effect of two forms of low-impact exercise on prepubertal changes in body composition and bone architecture. Weanling male rats were assigned to control (CON), bipedal stance (BPS), or wheel exercise (WEX) groups for 15 days until the onset of puberty. Distance travelled via WEX was recorded, food intake measured, and body composition quantified. Trabecular and cortical microarchitecture of the femur were determined by microcomputed tomography. WEX led to a higher lean mass and reduced fat mass compared to CON. WEX animals had greater femoral cortical cross-sectional thickness and closed porosity compared to CON. The different exercise modalities had no effect on body weight or food intake, but WEX significantly altered body composition and femoral microarchitecture. These data suggest that short-term mild voluntary exercise in normal prepubertal rats can alter body composition dependent upon the exercise modality.